ROLE OF MATHEMATICS IN CONTRIBUTING DEVELOPMENT OF CRITICAL THINKING ON STUDENTS FROM HISTORY UP TO NOW (British Journal of Global Ecology and Sustainable Development, 2025)
Authors of this paper draw attention to the importance of developing critical thinking in the process of education. Critical thinking skills should be owned by students. Therefore, schools should be responsible to develop and evaluate critical thinking skills through teaching and learning process at schools.